Diversity of mosses in some selected regions of Nagaland (North-East India), India - Sahu, Vinay; Singh, Harsh; Srivastava, Abhai K; Asthana, Ashish Kumar (Plant Science Today, 2022)
During an investigation on mosses of some underexplored regions of Nagaland, 121 taxa of mosses belonging to 74 genera and 29 families have been identified. Atrichum crispulum Schimp. & Besch. and Plagiothecium neckeroideum var. niitakayamae (Toyama) Z. Iwats. are new records for India. Five taxa namely Fissidens crassinervis var. laxus (Sull & Lesq.) A. Eddy., Barbula inaequalifolia Taylor, Amblystegium saxatile Schimp., Dicranum orthophylloides Dixon and Fabronia madurensis Dixon & Vard. are reported for the first time from Eastern Himalaya, while 57 taxa are new additions to Nagaland.